2014
DOI: 10.1093/icb/icu026
|View full text |Cite
|
Sign up to set email alerts
|

Self-burial Mechanics of Hygroscopically Responsive Awns

Abstract: We present the results of a combined experimental and theoretical investigation of the mechanics of self-burial of some plant seeds whose morphologies respond to environmental changes in humidity. The seeds of Erodium and Pelargonium have hygroscopically responsive awns that play a critical role in their self-burial into soil. The awn, coiled in a dry state, uncoils to stretch linearly under highly humid condition because of a tilted arrangement of cellulose microfibrils in one of the layers of the awn's bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…Moisture-responsive behaviors are widely spread in nature, such as moisture-responsive events of plants and fungi during the dispersion of seeds and spores 1 2 , the opening of pine cones, twisting and bending of wheat awns ( Triticum turgidum ) 3 4 5 6 . During the alteration of the environmental moisture content, i.e.…”
mentioning
confidence: 99%
“…Moisture-responsive behaviors are widely spread in nature, such as moisture-responsive events of plants and fungi during the dispersion of seeds and spores 1 2 , the opening of pine cones, twisting and bending of wheat awns ( Triticum turgidum ) 3 4 5 6 . During the alteration of the environmental moisture content, i.e.…”
mentioning
confidence: 99%
“…This indicated that awn length interacts with traits affecting seed dispersal in Siberian wildrye. Besides, some studies have demonstrated that environmental factors, such as wind, may affect seed dispersal under the aid of seed appendages, such as awns [23,41], which implies that awns may affect seed dispersal, especially under wild conditions. In our study, seed dispersal distance showed a negative correlation with seed length, indicating that longer seeds are not easily transported by seed dispersal agents.…”
Section: The Impact Of Seed Traits On Seed Dispersal Distancementioning
confidence: 99%
“…It is reported that larger seeds are disadvantageous during dispersal but contain more carbohydrates reserves, which facilitate seed germination and give rise to more vigorous seedlings than smaller ones [20,21]. A number of studies have shown that long and barbed awns assist seed dispersal by adhesion to animal fur [22][23][24]. However, reports on the contribution of awns on germination behavior remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the walls of the Erodium awn cells have reinforcing cellulose fibers arranged in a tilted helical pattern ( Figure 1B) so that the longitudinal axis of the helical fibers does not align with the cell axis. As a result, when the ambient humidity drops, plant tissues in the Erodium awn would shrink in volume due to hygroscopy, and their tilted helical fibers can direct this shrinking into a coiling motion Aharoni et al, 2012;Abraham and Elbaum, 2013;Elbaum and Abraham, 2014;Jung et al, 2014;Zhao et al, 2017). Similarly, the awn would uncoil when humidity increases, essentially creating a "drill bit" in the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%